Multicooperation of Turtle-inspired amphibious spherical robots - Liang Zheng; Yuke Ma; Hui Yu; You Tang (Scientific Reports)
Abstract It is challenging to achieve high-speed and accurate multicooperation of turtle-inspired amphibious spherical robots (ASRs) in turbid water and confined spaces when the robots are underwater movement with multiple degrees of freedom (MDOF). This paper innovatively proposes a control strategy for modelling and experimental platforms that can communicate and cooperate between multiple robots. First, a novel underwater kinematic model using the unit quaternion (UQ) algorithm is proposed based on attitude interpolation to realize MDOF movement. Then, the ASRs use a camera acquisition compartment to realize underwater target recognition and tracking by adjusting their motion trajectory. Finally, multirobot cooperation and three-dimensional (3-D) movement experiments using ASRs verifies the effectiveness of the proposed cooperation mode and 3-D underwater movement according to the control strategy implemented. The control strategy and experimental results presented in this paper can inspire the efficient communication and cooperation of multiple bionic robots, which are currently popular research topics.